2014
DOI: 10.1097/ta.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity prevents the development of acute traumatic coagulopathy

Abstract: Obesity prevents the development of ATC following hemorrhage shock. Complications associated with obesity following hemorrhagic shock may be attributed to the preserved hypercoagulable state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Previous work has shown that in animal models of trauma and human cohorts, obesity prevents prolongation of clot initiation, enhances fibrin cross-linking, and promotes clot strength following hemorrhagic shock. (12, 33) Several studies have also shown an interaction with obesity and platelet activity due to alterations in several pathways that invoke platelet activation. (34) Leptin, a signaling hormone produced by adipocytes has been shown to enhance platelet aggregation, promoting thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that in animal models of trauma and human cohorts, obesity prevents prolongation of clot initiation, enhances fibrin cross-linking, and promotes clot strength following hemorrhagic shock. (12, 33) Several studies have also shown an interaction with obesity and platelet activity due to alterations in several pathways that invoke platelet activation. (34) Leptin, a signaling hormone produced by adipocytes has been shown to enhance platelet aggregation, promoting thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…In our prior trial, 13 with higher observed VTE rates, BMI ranged from 30.6 to 32.8. In a rat obesity model, McCully et al 32 demonstrated that obese rats do not develop the acute coagulopathy of trauma after hemorrhagic shock and are hypercoagulable at baseline. Other authors 21 suggest that obesity decreases the effectiveness of enoxaparin prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Venous thromboembolism can be a major cause of organ failure after hemorrhage, and the risk of developing this complication is increased in obese trauma patients (68). For example, in Sprague-Dawley rats subjected to an uncontrolled hemorrhage (54), those fed a high-fat diet remained in a hypercoagulable state as compared to those fed a normal diet, which may play a role increasing the risk of thromboembolism. Characterized by insulin resistance and a hypercoagulable state, obese animals could be used to determine the impacts of stress hyperglycemia and thromboembolism on outcomes following hemorrhage.…”
Section: Obesity and Animal Models Of Critical Illnessmentioning
confidence: 99%